Assessment of current adhesives in class I cavity: Nondestructive imaging using optical coherence tomography and microtensile bond strength. Issue 9 (September 2015) - Makishi, Patricia; Thitthaweerat, Suppason; Sadr, Alireza; Shimada, Yasushi; Martins, Adriano Luis; Tagami, Junji; Giannini, Marcelo
Highlights Sealing performance was measured in five adhesives by optical coherence tomography. Sealing and bond strength performance within individual specimens were correlated. Interfacial defects increased after thermal aging. Increased interfacial defects tended to decrease the bond strength. Two- and three-dimensional images were useful in assessing bonding performance.